Pengaruh Kompensasi Dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada Perusahaan Timbul Jaya Tulungagung - Denok Eliana Manda Mubtadiin; Achmad Agus Prioyono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted at Timbul Jaya Tulungagung Company. The type of research used is quantitative with the method of distributing questionnaires. The sample used is 59 respondents who are all employees of Timbul Jaya Tulungagung Company. The data analysis method used in this research is instrument test, multiple linear analysis, classical assumption test, f test, t test, and determination test using SPSS tool. The variables used in this study are work productivity variables (dependent variable) while the independent variables are compensation and motivation.The results of this study conclude that the compensation variable has an effect on employee work productivity, motivation has an effect on employee work productivity. Compensation and motivation have a simultaneous effect on employee productivity. Keywords: Compensation, Motivation, and Employee Work Productivity.